2014
DOI: 10.1111/joor.12174
|View full text |Cite
|
Sign up to set email alerts
|

Maximum bite force following unilateral implant‐supported prosthetic treatment: within‐subject comparison to opposite dentate side

Abstract: Bite force is a significant component of chewing and masticatory function. The literature lacks studies that compare bite force values of implant-supported fixed bridges to natural dentition within same subjects. The objective of the study was to assess maximum occlusal bite force (MBF) among patients with an implant-supported fixed prosthesis and compare it to their opposite dentate side and also to determine the effect of gender, age and Body Mass Index (BMI) on maximum occlusal bite force. Forty patients (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
32
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 32 publications
8
32
1
4
Order By: Relevance
“…The use of a monolithic structure reduces the vulnerability of a cover layer, and a much less complex structure is expected . Because the average masticatory force at the molar region is 595 N, all of the tested materials present enough strength to be used in the posterior region; however, lithium disilicate exhibited the highest fracture resistance and the lowest failure probability of the materials tested in the present study.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The use of a monolithic structure reduces the vulnerability of a cover layer, and a much less complex structure is expected . Because the average masticatory force at the molar region is 595 N, all of the tested materials present enough strength to be used in the posterior region; however, lithium disilicate exhibited the highest fracture resistance and the lowest failure probability of the materials tested in the present study.…”
Section: Discussionsupporting
confidence: 87%
“…This CAD/CAM process allows an adequate marginal gap and the absence of air bubbles inside the structure of the material, increasing the fracture resistance of prostheses manufactured from CAD/CAM blocks compared to those that are hand‐processed by a technician . However, the implants’ success depends on the reliability of the prosthetic components and crown materials to support the occlusal loading, especially in the posterior regions of the jaw, where the average masticatory force reaches 538 N in women and 651 N in men …”
mentioning
confidence: 99%
“…In adults with natural dentition, it has been observed that the preferred chewing side is closely related to bite force . A study comparing bite force in patients with an implant‐supported fixed prosthesis and natural dentition on the opposite side found that MBF was significantly higher on the dentate side . However, despite these results, a number of factors remain insufficiently discussed in the literature.…”
mentioning
confidence: 99%
“…16 Common sense indicates, the more bone contact the more resistance to compression and tension to limit micromovement under occlusal load. Osseous cortex provides the most bone contact because it is very dense and without trabeculations.…”
Section: Crown To Implant Ratio and Bone Supportmentioning
confidence: 99%